The syndrome of transient epileptic amnesia. - Butler, C; Graham, K; Hodges, JR; Kapur, N; Wardlaw, J; Zeman, A (2007)
OBJECTIVE: Transient amnesia can be the principal manifestation of epilepsy. This diagnosis, however, is seldom suspected by clinicians and remains controversial. The amnestic attacks are often associated with persistent memory complaints. This study was designed to provide the first description of transient epileptic amnesia in a substantial series of patients. METHODS: Fifty patients were recruited over 18 months using the following diagnostic criteria: (1) recurrent, witnessed episodes of amnesia; (2) other cognitive functions intact during attacks; and (3) compelling evidence of epilepsy. We assessed clinical features and performed neuropsychological evaluation in cases and 24 matched control subjects. RESULTS: Transient epileptic amnesia develops in later life (mean onset, 62 years). Amnestic episodes are frequent (median, 12/year), brief (median duration, 30-60 minutes), and often occur on waking (37/50 cases). Epilepsy was the initial specialist diagnosis in only 12 of 50 cases. Attacks ceased on anticonvulsant medication in 44 of 47 treated patients. A total of 40 of 50 cases described persistent memory difficulties. Despite normal performance on standard memory tests, patients exhibited accelerated forgetting of verbal and visual material over 3 weeks by comparison with matched control subjects (p < 0.001). They also showed loss of autobiographical memories for events extending back over 40 years (p < 0.05). INTERPRETATION: We propose that transient epileptic amnesia is a distinctive epilepsy syndrome, typically misdiagnosed at presentation and associated with accelerated long-term forgetting and autobiographical amnesia. The syndrome is of clinical and theoretic importance.